(untitled) (Communications in Computational Physics, 2019)
A full approximation storage multigrid method has been shown to improve the convergence properties of the D2Q9 BGK lattice Boltzmann method [14]. In this paper we extend the method to the multiple relaxation time collision model due to its improved stability. The new method is validated using Poiseuille flow. The method is then extended to three dimensions. The efficiency of the V-cycle and W-cycle multigrid schedules and the under-relaxed Jacobi and Gauss Seidel multigrid smoothers are reported for the two and three dimensional models for lid driven cavity flow.